2021
DOI: 10.1186/s13028-021-00588-w
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic fauna of Eurasian beavers (Castor fiber) in Sweden (1997–1998)

Abstract: Background The parasitic fauna of beavers (Castor fiber and C. canadensis) has been well studied in many parts of their respective areas of distribution. In Scandinavia there have, however, been limited investigations conducted on the parasites of beavers in recent times. The present study is the first quantitative survey of parasites on beavers living in Sweden and elsewhere in Scandinavia. We investigated the parasitic fauna of the Eurasian beaver (C. fiber) in a North–South gradient in Swede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The Hungarian population was almost exclusively originated from Bavaria (Bajomi 2011 ). This bottleneck effect might have resulted the loss of more than one of the beaver parasites as it was proposed by Åhlen et al ( 2021 ) in Sweden. As parasites represent significant component of the biodiversity and ecosystem, the conservation efforts should focus not only on host species but also on their parasites.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The Hungarian population was almost exclusively originated from Bavaria (Bajomi 2011 ). This bottleneck effect might have resulted the loss of more than one of the beaver parasites as it was proposed by Åhlen et al ( 2021 ) in Sweden. As parasites represent significant component of the biodiversity and ecosystem, the conservation efforts should focus not only on host species but also on their parasites.…”
Section: Resultsmentioning
confidence: 82%
“…Among endoparasite helminth species, the flatworms Psilotrema castoris , Stichorchis subtriquetrus (Demiaszkiewicz et al 2014 ), Echinococcus multilocularis , Taenia martis (Campbell-Palmer et al 2015 ), Fasciola hepatica (Shimalov and Shimalov VT 2000); the nematode Travassosius rufus (Bystrianska et al 2021 ), Trichostrongylus capricola (Demiaszkiewicz et al 2014 ), Calodium hepaticum (Mészáros and Kemenes 1973 ; Fuehrer 2014 ), Trichinella spiralis (Różycki et al 2020 ) and Trichinella britovi (Seglina et al 2015 ) were found in C. fiber . Among ectoparasites, there are fur mites from the genus Schizocarpus , Demodex follicule mites (Izdebska et al 2016 ); two hard tick species Ixodes hexagonus (Haitlinger 1991 ) and Ixodes apronophorus (Kadulski 1998 ) and a unique epidermal tissue feeding beetle, Platypsyllus castoris (Åhlen et al 2021 ). Beavers can serve as a host for a wide range of rodent-related pathogens as well.…”
Section: Introductionmentioning
confidence: 99%